ACCOMPANIMENT OF REGISTRATION TRADEMARKS STEAK JOBS - Niken Dwi Anggawati; Windi Afdal (ConCEPt - Conference on Community Engagement Project, 2022)
Trademark Rights are Intellectual Property Rights that often used in daily life and very important for business actors where they become differentiators from other products and or services. Brand rights can also provide protection for the owner to avoid imitation from competitors. But the fact is that there are still many business actors who have not registered their trademarks for their businesses because of the lack of knowledge about brands. One of them is Steak Jobs. The owner of Steak Jobs objected to the relatively high cost of registering a mark if it was registered by an IPR consultant and the complicated process of registering a trademark if it was done by himself. In this case, Steak Jobs requires legal assistance in the form of assistance in registering its trademark. The method of implementation carried out by the author is in the form of a survey to find partners, interviews to find out the problems being faced, providing insight to partners related to the trademark registration mechanism, collecting the necessary documents and registering the mark online on the merek.dgip.go.id site. The output of this project is assistance for the registration of the Steak Jobs Trademark which is submitted online to the Directorate General of Intellectual Property, the issuance of an online application receipt for the registration of the Steak Jobs Trademark until the trademark registration application is declared complete and enters the announcement stage as a result of the assistance for the registration of the Steak Jobs Trademark.